Using iPad 2 - Smith, Bud E. (Que, 2011)
"The Using iPad 2 video is the ultimate way to learn about your iPad 2. Sit back and let iPad expert Bud Smith show you, step-by-step, how to get the most out of your new addiction, er, iPad. Bud shows you everything from the basics (on-screen gestures, moving icons and so on) to involved topics, such as setting up a network connection, syncing with your computer, setting up email and much, much more. Why read a book when you can have the author show you how to do it? Total running time is about 3 hours."--Resource description page.